What Is and What Should Be: Sociology of Studying Russia in the U.S. - A. P. Tsygankov (Международная аналитика)
The article examines the process of knowledge formation about Russia in American academia since the end of the Cold War. The article’s hypothesis is that knowledge formation largely reflects the social and national and cultural conditions of the country and its research community. Although many scholars strive for objectivity and ethical detachment from the object of their research, they most often approach its study from positions that reflect and project the interests and values of the societies in which they work. This hypothesis is formulated within the framework of the sociological approach to knowledge formation undertaken in the article, which involves understanding the conditions of its formation and the social demands that it meets. American knowledge about Russia, which they have long viewed and continue to view as a threat and challenge to the interests and values of the United States, bears the stamp of national assumptions, preferences, beliefs, and emotions. In studying reality, they are far from always able to free themselves from the American understanding of what should be, projecting into their research how, in their opinion, Russia should develop. Since the second half of the 2000s, this gap has been widening. Compared to the Cold War, knowledge about Russia in America has lost its former status of priority and privilege, and has become more politicized, especially in matters aﬀecting international security and the politics of values. In addition, this knowledge has been integrated into generally accepted theories of international relations and comparative politics in the West.These changes reflect Russia’s declining status in the international hierarchy compared to the United States and the growing conviction of American social scientists in the universal validity of their approaches and theories. Contemporary Russia is increasingly perceived as developing in the wrong direction, threatening Western “liberal democratic” values and security, and, with its desire to be an “empire,” the very structures of modern society. Although not all American researchers share such concepts and theories, the latter express the mood of the mainstream in both politics and science. The final part sums up the results and discusses the possibilities of forming less biased and ideologically loaded knowledge about Russia. Approaches to obtaining such knowledge in the United States exist, although they do not dominate.